Valproic Acid Regulates HR and Cell Cycle Through MUS81-pRPA2 Pathway in Response to Hydroxyurea - Su, Benyu; Lim, David; Tian, Zhujun; Liu, Guochao; Ding, Chenxia; Cai, Zuchao; Chen, Chen; Zhang, Fengmei; Feng, Zhihui (Frontiers in Oncology, 2021)
Breast cancer is the primary problem threatening women's health. The combined application of valproic acid (VPA) and hydroxyurea (HU) has a synergistic effect on killing breast cancer cells, but the molecular mechanism remains elusive. Replication protein A2 phosphorylation (pRPA2), is essential for homologous recombination (HR) repair and cell cycle. Here we showed that in response to HU, the VPA significantly decreased the tumor cells survival, and promoted S-phase slippage, which was associated with the decrease of pCHK1 and WEE1/pCDK1-mediated checkpoint kinases phosphorylation pathway and inhibited pRPA2/Rad51-mediated HR repair pathway; the mutation of pRPA2 significantly diminished the above effect, indicating that VPA-caused HU sensitization was pRPA2 dependent. It was further found that VPA and HU combination treatment also resulted in the decrease of endonuclease MUS81. After MUS81 elimination, not only the level of pRPA2 was abolished in response to HU treatment, but also VPA-caused HU sensitization was significantly down-regulated through pRPA2-mediated checkpoint kinases phosphorylation and HR repair pathways. In addition, the VPA altered the tumor microenvironment and reduced tumor burden by recruiting macrophages to tumor sites; the Kaplan-Meier analysis showed that patients with high pRPA2 expression had significantly worse survival. Overall, our findings demonstrated that VPA influences HR repair and cell cycle through down-regulating MUS81-pRPA2 pathway in response to HU treatment.